Skopje’s Mega Block: Modern Architecture as an Art of Grafting - Meri Batakoja (My University, 2018)
The formative idea of “grafting” or “graftage” is originally a horticultural technique of inserting tissues from one plant to another in order for them to join together and continue to grow as a single plant. The technique of “graftage” in architectural context would mean that a new architecture is being interpolated over an old one, but by a set of treatments used, the different architectural interventions function as a single entity. It is presented in this text in the context of modern architecture of one singular urban block of Skopje.
Keywords: grafting, modern architecture, Skopje, context